Microplastics of different shapes increase seed germination synchrony while only films and fibers affect seed germination velocity - Lozano, Yudi M.; Caesaria, Putri U.; Rillig, Matthias C. (Frontiers in Environmental Science, 2022)
Microplastics enter the soil in a variety of shapes and polymer types altering soil properties with known consequences for plant growth. However, the effects of a range of different microplastic shapes and types on seed germination are mostly unknown. Here, we established a glasshouse experiment that included 12 microplastic types representing different shapes (fibers, films, foams and fragments) and polymers, and mixed each of them with soil at a concentration of 0.4 % (w/w). Fifty seeds of Daucus carota were sown and monitored for 49 days to evaluate different germination parameters. Our results showed that microplastic films and fibers decrease seed germination velocity as they may affect soil water status, likely interfering with different phases of seed germination: Seeds may imbibe toxic microplastic leachates, and be affected by a physical blockage; testa rupturing may be delayed as this also depends on water uptake. Microplastic toxic leachates may affect activity of enzymes key for seed germination, and delay embryo growth and radicle emergence. Microplastics, irrespective of their shape and polymer type, increase synchrony of seed germination, which might be linked with microplastics exerting a mild stress on seeds. The final percentage of germination was not affected by microplastics in soil, implying that microplastics did not affect seed viability. Our results showed that microplastics affect seed germination mainly as a function of their shape.